Endurance swimmers: tips for tapering for an open-water race - Kostich, A.
Tapering for long-distance open-water competition is nothing like tapering for a pool race. While the idea of giving your body a break and allowing it to recover in time for a peak performance is the same, the approach to open-water tapering needs to take into consideration the maintenance of endurance. In open-water swimming, competitors must rely on endurance more than speed to successfully complete their challenge. Races can vary from 800 meters (a half-mile) to 25 miles, either of which requires a lot more endurance over speed. So given that tapering involves the decrease in intensity and distance covered in the weeks leading up to an event, how does one gauge how much to cut down without losing a hard-earned endurance background? To begin, take a taper model of 100:75:50 and see how much distance you will be covering at the height of your taper (when you will be swimming 50 percent of your normal workout distance). For example, if your typical everyday workout were 4,000 meters, a taper workout in your second week would be 2,000 meters. Now take the ocean race you plan on completing. Is it over 2,000 meters or not? If it is less, 2,000 meters is a good distance to pare down to. However if your race is 2.4 miles or four miles or more, your taper needs to be reworked so that the distance covered is sustained. Assuming your race is 2.4 miles (the first leg of an Ironman triathlon), the very least you should be swimming on a daily basis during your taper is about two miles (3,000 meters). As in any taper, it is important to warm up luxuriously, and allow enough time to warm down as well. However, whereas in a typical taper you might mix speed work, drills and short pace sets, in an open-water taper it is important to maintain a steady active heart rate over a longer period of time (instead of explosive short bursts of energy and speed). For instance, rather than do 3x100#s pace @ 10 seconds' rest or 4x25#s sprint @1:00 (as suggested in the last column), a better set to do in the days before an open-water race would be: 300 @ 15 secs rest (85% effort) 200 @ 10 secs rest (90% effort) 100 @ 5 secs rest (95%effort) 100@ 10 secs rest (90%effort) 200 @ 15 secs rest (85%effort) (TOTAL: 900 meters) Relatively, this is a long set for a taper workout. But you are never sprinting at 100 percent effort, only concentrating on covering the distance quickly and comfortably while getting your heart rate up over a 10- to 15-minute period (your race will last a lot longer than that, so this is a good preparatory drill). Granted, some sprinting taken from a typical taper workout can be a good way to increase speed and develop quick reflexes necessary for mid-race pace changes or sprints to pass your competitors, but you should be doing that in addition to yardage-covering sets like the one above. Open-water tapers need not last two or three weeks (the length of a typical pool-swimmer's taper). One week is usually plenty of time to feel rested and recovered if you are used to endurance training throughout the season. In fact, an open-water swimmer preparing for a five- to 10-mile race need only pare down the distance and intensity of his workouts maybe three days before the event. In such extreme high-endurance events, I prefer to take the day prior to the race off completely (as long as I have enough time to warm up 30 minutes the morning of the event itself). This full day off forces your body to rest and recover (even if you think you may not need it, you might), and your consistently fatigued muscles will feel fresher with a full 24 hours of idle rest. Keep in mind that open-water swims are a lot tougher on your body than pool racing, and as such tapering need not be as delicate or precise a feat. By nature, your body is equipped to handle more stress than the typical sprinter or pool swimmer. While rest and recovery is equally important, it's not the end of the world if you don't hit your taper perfectly (you can rely on your endurance background to power your way through a long race). But if you can pull off a great taper that allows you to feel good and increase your speed while not sacrificing any endurance, you will be pleasantly surprised at the outcome.